Menstrual cycle patterns of Indonesian adolescents - Imasari Aryani; Ulfa Puspita Rachma; Evie Rokhayati; Annang Giri Moelyo (Indonesian Pediatric Society, 2018)
Background Adolescents often experience menstrual irregularity in the first few years after menarche. Abnormal menstrual cycles may increase the risk of polycystic ovary syndrome. Objective To determine the menstrual cycle patterns of adolescent females in Indonesia and associated factors. Methods This cross-sectional study was conducted at two senior high schools in Surakarta, Central Java, from September to October 2016. Subjects were healthy female students whose parents have given written informed consent. Girls taking hormonal drugs or with chronic diseases were excluded. Subjects filled questionnaires on menstrual cycle, diet, ethnicity, and physical activity. All subjects underwent anthropometric measurements (height and weight). Kruskal-Wallis test was used for data analysis. Results Four hundred and forty-four subjects met the inclusion criteria. Mean age at menarche was 12.27 (SD 1.08) years. Mean menstrual cycle length was 31.1 (SD 6.5) days. Abnormal menstrual cycle occurred in 30.6% of subjects (24.5% oligomenorrhea, 5.9% polymenorrhea, and 0.2% amenorrhea). Ethnicity (Javanese, Chinese, or Arab) was significantly associated with menstrual cycle category (P<0.05). Girls with Chinese ethnicity having the largest proportion of oligomenorrhea. Other factors (body mass index, age, age at menarche, nutritional status, physical activity, and fat intake) were not found to be associated with menstrual cycle abnormalities. Conclusion Menstrual abnormalities, especially oligomenorrhea, are common in Indonesian adolescent girls. Oligomenorrhea is more frequent in girls of Chinese ethnicity, compared to those of Javanese or Arab ethnicity.